Pengaruh Senam Lansia terhadap Penurunan Tekanan Darah Lansia Penderita Hipertensi di Puskesmas Wara Palopo - Grace Tedy Tulak (LP3M Universitas Muhammadiyah Makassar)
This research is a quantitative pre-experimental with a pretest-posttest design. Data collected by the observation sheet with a sample of 36 people obtained by total sampling. Results of the study were tested using paired-samples test obtained a value of P 0.05, which means there is elderly gymnastics influence on blood pressure reduction.Advanced age is a natural process of the growth. Blood pressure is the necessary power so that blood can flow in the blood vessels and circulation reached all the tissues of the human body. Hypertension or high blood pressure is an abnormal increase in blood pressure in the arteries continuously over a period. Gymnastics elderly is a form of aerobic exercise is beneficial for the elderly. Gymnastics elderly people who can help to maintain the balance of blood pressure. This study aimed to analyze the influence of gymnastics elderly to decrease blood pressure in elderly hypertensive patients PHC Wara Palopo 2016.